Notes on the morphology of the musculature of the salivary syringe and neck region of bees - Wille, Alvaro (1970)
In a comparative study of the musculature of the salivary syringe and neck region of bees, forty genera, representing six families, were dissected. Some interpretations of the phylogeny of the muscles are discussed. Evolutionary tendencies and probable trends of specialization were found in the following three muscles: dilatar of the salivary syringe, inferior phragmatic levator of the head, and phragmatopleural muscle of the prothorax.